PEMBANGUNAN HUKUM DENGAN PENDEKATAN SOSIO-LEGAL - Hartono, Hartono (Ekonomi Syariah STAI Sangatta Kutai Timur, 2019)
True law is not born from empty and empty space, people as legal users participate in coloring the law itself. The socio-legal approach puts forward two aspects; First the ability to analyze each product of textual study legislation, the articles in the legislation and policy can be analyzed critically and explained the meaning and implications for legal subjects (including marginalized groups). Secondly, the ability to interact with other legal sciences is also the development of global law today. The use of the socio-legal approach is actually intended to gain a new understanding that the law is not monoistic but the law can be seen also interdisciplinary, some experts also see that the law has many faces, in line with the interdisciplinary study, in fact legal pluralism is true, this can be seen from the paradigm that he built namely legal pluralism is associated with the